Visualization of the radiofrequency lesion after pulmonary vein isolation using delayed enhancement magnetic resonance imaging fused with magnetic resonance angiography. Issue 3 (27th November 2014) - Kiuchi, Kunihiko; Okajima, Katsunori; Shimane, Akira; Yokoi, Kiminobu; Teranishi, Jin; Aoki, Kousuke; Chimura, Misato; Tsubata, Hideo; Miyata, Taishi; Matsuoka, Yuuki; Toba, Takayoshi; Ohishi, Shogo; et al.
Abstract: Background: The radiofrequency (RF) lesions for atrial fibrillation (AF) ablation can be visualized by delayed enhancement magnetic resonance imaging (DE‐MRI). However, the quality of anatomical information provided by DE‐MRI is not adequate due to its spatial resolution. In contrast, magnetic resonance angiography (MRA) provides similar information regarding the left atrium (LA) and pulmonary veins (PVs) as computed tomography angiography. We hypothesized that DE‐MRI fused with MRA will compensate for the inadequate image quality provided by DE‐MRI. Methods: DE‐MRI and MRA were performed in 18 patients who underwent AF ablation (age, 60±9 years; LA diameter, 42±6 mm). Two observers independently assessed the DE‐MRI and DE‐MRI fused with MRA for visualization of the RF lesion (score 0–2; where 0: not visualized and 2: excellent in all 14 segments of the circular RF lesion). Results: DE‐MRI fused with MRA was successfully performed in all patients. The image quality score was significantly higher in DE‐MRI fused with MRA compared to DE‐MRI alone (observer 1: 22 (18, 25) vs 28 (28, 28), p <0.001; observer 2: 24 (23, 25) vs 28 (28, 28), p <0.001). Conclusions: DE‐MRI fused with MRA was superior to DE‐MRI for visualization of the RF lesion owing to the precise information on LA and PV anatomy provided by DE‐MRI.